Social need of the application of a Didactic Strategy for the learning of orthography with emphasis in the accentuation of words (REDEL. Revista Granmense de Desarrollo Local, 2021)
This investigation makes of in front of a component the Mixed Center's bench of problems Amador Liens Cabrera of the municipality the Ox Arrives. It is specified like objective in her: The elaboration of a didactic strategy for the learning of orthography with emphasis in the accentuation of words. During the investigating, process him emperor theoretic methods, empiricists and statisticians – mathematicians. The referent theoreticians of the process of teaching systematize – learning of the Spanish subject of study – Literature in the pre-university education themselves in the first epigraph, with emphasis in the accentuation of words. One second the epigraph enables approaching a didactic strategy that you modify this present-day status. The attained results allow declaring the effectiveness of the application of the proposed strategy.
Keywords: didactic strategy; accentuation of words; learning of orthography; spell